"GaI": A versatile reagent for the synthetic chemist. - BAKER, ROBERT (My University, 2005)
The current renaissance in main group chemistry has been fuelled by the remarkable array of fundamentally interesting yet synthetically applicable low oxidation state p-block compounds that have appeared over the last decade. Their syntheses generally require the ready availability of low oxidation state element halide precursors. In the case of gallium this is provided by the simple to prepare reagent, “GaI”, which since it was first reported in 1990, has been utilised in areas as varied as organic synthesis and gallium cluster construction. This article tracks the history of this extraordinary material and highlights its synthetic diversity; hopefully allowing the reader to envisage its application to aspects of their own research fields.
PUBLISHED
Keywords: Chemistry